Machinability studies on laser-sintered iron-silicon carbide metal matrix composites using wire electrical discharge machining. (1st January 2012) - Srinivasa, C.K.; Vinod, A.R.; Shashikumar, P.V.
This paper focuses on wire electrical discharge machining (WEDM) of iron and iron-1, 2, 3 and 5 wt.% SiC composites produced by direct metal laser sintering (DMLS) process. Discharge currents of 9, 13 and 18 A were adopted during machining while the wire speed was maintained at 90 mm/min. Results have indicated that discharge current, laser scan speed and extent of silicon carbide content in the composites, had a greater influence on the machining time and surface roughness of the machined surface.